Gelatin-methacryloyl hydrogels containing turnip mosaic virus for fabrication of nanostructured materials for tissue engineering - González-Gamboa, Ivonne; Velázquez-Lam, Edith; Lobo-Zegers, Matías José; Frías-Sánchez, Ada Itzel; Tavares-Negrete, Jorge Alfonso; Monroy-Borrego, Andrea; Menchaca-Arrendondo, Jorge Luis; Williams, Laura; Lunello, Pablo; Ponz, Fernando; Alvarez, Mario Moisés; Trujillo-de Santiago, Grissel (Frontiers in Bioengineering and Biotechnology, 2022)
Current tissue engineering techniques frequently rely on hydrogels to support cell growth, as these materials strongly mimic the extracellular matrix. However, hydrogels often need ad hoc customization to generate specific tissue constructs. One popular strategy for hydrogel functionalization is to add nanoparticles to them. Here, we present a plant viral nanoparticle the turnip mosaic virus (TuMV), as a promising additive for gelatin methacryloyl (GelMA) hydrogels for the engineering of mammalian tissues. TuMV is a flexuous, elongated, tubular protein nanoparticle (700–750 nm long and 12–15 nm wide) and is incapable of infecting mammalian cells. These flexuous nanoparticles spontaneously form entangled nanomeshes in aqueous environments, and we hypothesized that this nanomesh structure could serve as a nanoscaffold for cells. Human fibroblasts loaded into GelMA-TuMV hydrogels exhibited similar metabolic activity to that of cells loaded in pristine GelMA hydrogels. However, cells cultured in GelMA-TuMV formed clusters and assumed an elongated morphology in contrast to the homogeneous and confluent cultures seen on GelMA surfaces, suggesting that the nanoscaffold material per se did not favor cell adhesion. We also covalently conjugated TuMV particles with epidermal growth factor (EGF) using a straightforward reaction scheme based on a Staudinger reaction. BJ cells cultured on the functionalized scaffolds increased their confluency by approximately 30% compared to growth with unconjugated EGF. We also provide examples of the use of GelMA-TuMV hydrogels in different biofabrication scenarios, include casting, flow-based-manufacture of filaments, and bioprinting. We envision TuMV as a versatile nanobiomaterial that can be useful for tissue engineering.